Water option contracts for climate change adaptation in Santiago, Chile. Issue 2 (17th February 2018) - Vicuña, Sebastián; Gil, Marina; Melo, Oscar; Donoso, Guillermo; Merino, Pablo
ABSTRACT: Climate change–induced extreme events pose an important challenge for urban water managers. In Santiago (Chile), the total cost of such events can be reduced by an option contract that sets ex ante water prices and water volumes to be traded when certain triggering conditions are met. This article discusses two types of option contracts: water leasing to trade water from agriculture to urban uses during droughts; and a savings option contract to reduce urban water consumption during short-term turbidity events. We find that water option contracts are flexible instruments that improve the distribution of hydrological risks.